Análisis de las Anomalías en el inicio y el término de la estación lluviosa en Centroamérica y su relación con los océanos Pacífico y Atlántico Tropical - Alfaro Martínez, Eric J.; Cid Serrano, Luis Ramón (1999)
It is estimated the star, end and duration of the rainy season for 37 gauge stations located mainly on the Pacific Slope in Central America. The relation of these aspects with the sea surface temperature of the Tropical North and South Atlantic and Tropical Eastern Pacific was studied by means of a cross correlation and an anomalies analysis. The star of the rainy season was influenced mainly by the Tropical North Atlantic with early (late) starts related with warm (cold) conditions in this index. The Tropical Eastern Pacific was related mainly with the end of the rainy season with early (late) ends related with warm (cold) conditions in this oceanic zone. Finally, the Tropical North Atlantic was the main influence on the duration of the rainy season. It was observed a longer (shorter) period of rains related with warm (cold) conditions on this index. Universidad de Costa Rica/[112-99-305]/UCR/Costa Rica Universidad de Costa Rica/[805-94-204]/UCR/Costa Rica Universidad de Costa Rica/[805-98-506]/UCR/Costa Rica UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro de Investigaciones Geofísicas (CIGEFI) UCR::Vicerrectoría de Docencia::Ciencias Básicas::Facultad de Ciencias::Escuela de Física